ChemInform Abstract: Catalyst‐Controlled Chemoselective Arylation of 2‐Aminobenzimidazoles. Issue 12 (14th March 2013) - Ueda, Satoshi; Buchwald, Stephen L.
Abstract An orthogonal set of conditions for the selective arylation steps is developed.